Severe xanthomatosis associated with familial apolipoprotein E deficiency. - Feussner, Giso (Journal of clinical pathology, 1996)
AIM: To present the clinical, dermatological, and histological features of a patient with generalised xanthomatosis, familial apolipoprotein (apo) E deficiency, and unusual type III hyperlipoproteinaemia (HLP). METHODS: The underlying molecular defect was disclosed using molecular biological techniques. The unusual xanthomas were histologically analysed and the morphology of the abnormal lipoprotein particles examined using electron microscopy. RESULTS: A 10 base pair deletion in exon 4 of the proband's apo epsilon gene (base pairs 4037-4046 coding for amino acids 209-212 of the mature protein) was identified. This is predictive for a reading frameshift encoding a premature stop (TGA) in codon 229. The mutation is responsible for delayed catabolism of atherogenic lipoprotein remnants, lipid storage in monocyte/macrophages, and phenotypic expression of xanthomatosis early in life. CONCLUSIONS: Familial apo E deficiency is a rare genetic disease which offers the unique opportunity to study the impact of apo E on lipoprotein metabolism and development of atherosclerosis in humans.
Elektronische Reproduktion der Druck-Ausgabe 18. April 2016
Gesehen am 27.01.2025